An empirical study of the challenging roles of psychiatric nurses at in-patient psychiatric facilities and its implications for nursing education - Perrene Dale Joubert; Raisuyah Bhagwan (Elsevier, 2018)
Nurses constitute the largest group of health care professionals who care for mental health care users in the psychiatric services field. This places them at the crucial juncture of providing quality care whilst trying to manage the challenges that arise with this patient group. Part of dealing with this requires that nursing education be aware not only of the multifaceted roles of psychiatric nurses but the unique and sometimes daunting challenges involved in nursing mentally ill patients.Whilst the roles of psychiatric nurses have received growing attention; little research exists on the roles and challenges associated with psychiatric nursing at local in-patient mental health care facilities. The current study explored the roles of psychiatric nurses at in-patient facilities, the challenges associated with same and the difficulties associated with caring for mental health care users.A quantitative descriptive design was used to survey 396 psychiatric nurses. A census of 436 nurses formed the sample as the entire population of psychiatric nurses at in-patient psychiatric facilities in KwaZulu-Natal was sampled.The most common issues faced in psychiatric nursing practice were that "mental health care users deny mental illness" and the challenges associated with exposure to patients' unpredictable behaviour. Of significance was that nurses were also exposed to increased levels of aggression and violence. Psychiatric nurses reported experiencing feelings of anger and frustration, as well as high levels of burnout. Whilst psychiatric nurses indicated that they were suitably trained to deal with mental health care users, most supported the need for further training. Keywords: Mental health nursing or psychiatric nursing, Mental health care practitioner, Mental health care user, Psychiatric nurse